Influence of Perceived Trust, Convenience and Security on The Use of Mobile Banking - Siti Munfaqiroh; Leonardo Calvin Pareira; Bunyamin Bunyamin (Lafadz Jaya Publisher, 2025)
The aim of this research is to determine and analyze the influence of perceptions of trust, convenience and security on the use of mobile banking. This research uses quantitative data with a causal approach. The population used in this research was 817 active STIE Malangkucecwara students who used the mobile banking application. The sampling technique in this research used incidental sampling. And based on the Slovin formula, the samples in this study were 90 samples. In this research, the data analysis methods used include the classic assumption test which includes, among others; normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test as well as hypothesis testing which includes the coefficient of determination test and t test. Based on the research results, it shows that perceptions of trust, perceptions of convenience, and perceptions of security influence the use of mobile banking.